Relationship between Financial Literacy Variables and Materialism of Millennials in a Selected South Africa Municipality : Array - Fielies, Hein; Mbukanma, Ifeanyi (The Journal of Accounting and Management, 2022)
Purpose: This study's objective was to statistically ascertain the relationship between financial literacy variables and materialism of millennials in the Phokwane Local Municipality, South Africa. This objective was motivated based on the gap in the literature as it concerns how financial literacy relates to millennial materialism in South Africa. Method: A quantitative research method was adopted with a focus target population of millennials (ages 22 to 44 years old) in Phokwane Local Municipality using purposive and convenient sampling techniques. A self-administered questionnaire through google form was used to obtain responses from the participants, and the study conducted an inferential (Pearson Correlation) statistical analysis using SPSS Version 26. Findings: The study revealed that all the financial literacy variables are strongly positively correlated except money attitude with negative correlation. The implication of the positive correlation indicates that the more knowledge the millennial has with one financial literacy variable, the more they tend to have in other variables except for their attitude towards money, which partly define their personality as millennials. Secondly, the relationship between money management, financial planning, financial products, savings, and investment is negatively correlated with millennials' materialism. This negative correlation indicates that even though millennials are financially literate, they are still materialistic. Recommendations: Policymakers and stakeholders in charge of financial literacy and savings campaigns in South Africa should focus more on the initiatives that promote the application and implementation of financial literacy knowledge and financial discipline by millennials and other active members of South African households.